La "Diuinatio in scribenda historia" de Nebrija - Maestre Maestre, José María (Euphrosyne: Revista de filología clássica, 1995)
The present article offers a new interpretation of the Diuinatio in scribenda historia which appears as a praefatio at the beginning of Nebrija’s historiographical works: the opusculum is a veiled attack against Lucius Marineus Siculus, who, like the Spanish humanist, aspired to compose in Latin the History of the Catholic Monarchs. Our research comprises not only an analysis of the historical context in which the Diuinatio in scribenda historia is written, but also a profound philological study of it, in which the classical world and, specifically, Cicero's Diuinatio in Quintum Caecilium become two key subjects.